Innovation of Islamic Education through Digitalization: Answering Global Challenges with Progressive Solutions - Rochmah, Arfayza Maulia; Inayati, Nurul Latifatul (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
Globalization and digitalization have significantly transformed the educational landscape, presenting both opportunities and challenges for contemporary learning systems. As education becomes increasingly interconnected, it demands a balance between technological innovation and the preservation of cultural and moral values. This study aims to analyze how Islamic education can adapt and innovate through digitalization to respond to global challenges while maintaining its moral and spiritual foundations. The research employs a qualitative descriptive method through an in-depth literature review and analysis of digital practices implemented in Islamic educational institutions. The findings reveal that the strategic integration of digital technology with Islamic values enhances the quality of learning, administrative efficiency, and student engagement. Tools such as artificial intelligence, online platforms, and virtual classrooms support personalized learning and improve institutional performance. Furthermore, the study highlights the importance of performance management, teacher digital competence, and ethical use of technology to ensure the sustainability of quality Islamic education in the digital era. With appropriate adaptation, innovation, and value-based digital transformation, Islamic education can remain relevant, competitive, and progressive amidst rapid global change.